Identification of Splicing Quantitative Trait Loci (sQTL) in Drosophila melanogaster with Developmental Lead (Pb(2+)) Exposure. - Qu, W.; Gurdziel, K.; Pique-Regi, R.; Ruden, D.M. (Frontiers in genetics, 2017)
Lead (Pb) poisoning has been a major public health issue globally and the recent Flint water crisis has drawn nation-wide attention to its effects. To better understand how lead plays a role as a neurotoxin, we utilized the Drosophila melanogaster model to study the genetic effects of lead exposure during development and identified lead-responsive genes. In our previous studies, we have successfully identified hundreds of lead-responsive expression QTLs (eQTLs) by using RNA-seq analysis on heads collected from the Drosophila Synthetic Population Resource. Cis-eQTLs, also known as allele-specific expression (ASE) polymorphisms, are generally single-nucleotide polymorphisms in the promoter regions of genes that affect expression of the gene, such as by inhibiting the binding of transcription factors. Trans-eQTLs are genes that regulate mRNA levels for many genes, and are generally thought to be SNPs in trans-acting transcription or translation factors. In this study, we focused our attention on alternative splicing events that are affected by lead exposure. Splicing QTLs (sQTLs), which can be caused by SNPs that alter splicing or alternative splicing (AS), such as by changing the sequence-specific binding affinity of splicing factors to the pre-mRNA. We applied two methods in search for sQTLs by using RNA-seq data from control and lead-exposed w(1118)Drosophila heads. First, we used the fraction of reads in a gene that falls in each exon as the phenotype. Second, we directly compared the transcript counts among the various splicing isoforms as the phenotype. Among the 1,236 potential Pb-responsive sQTLs (p < 0.0001, FDR < 0.39), mostly cis-sQTLs, one of the most distinct genes is Dscam1 (Down Syndrome Cell Adhesion Molecule), which has over 30,000 potential alternative splicing isoforms. We have also identified a candidate Pb-responsive trans-sQTL hotspot that appears to regulate 129 genes that are enriched in the "cation channel" gene ontology category, suggesting a model in which alternative splicing of these channels might lead to an increase in the elimination of Pb(2+) from the neurons encoding these channels. To our knowledge, this is the first paper that uses sQTL analyses to understand the neurotoxicology of an environmental toxin in any organism, and the first reported discovery of a candidate trans-sQTL hotspot.